Characterization of students who use piercings in Cali, Colombia (Colombia Medica, 2011)
Objetive: To know from a sample of secondary students between the 6th and 12th grades in four schools in the city of Santiago de Cali from different socio-economic levels, the characterization of their social demographic variables and the factors that motivated them to use piercings.Materials and methods: A 15-question survey was applied to 219 high school students who wore piercings, and an indepth interview was made to 10% of the sample.Results: From the 2120 secondary students from the four schools in different socio-economic levels that complied with the inclusion criteria for the study, 219 students (10.33%) used piercings, with their use predominating in the high, medium, and low stratums among young men, 16 years of age. These piercings were usually located in the earlobes and tongue, and were placed there at the shops where they bought them.Conclusion: The factors that influenced the decision to use the piercings were: because they liked them, they improved their image, it was fashionable, and because of the desire to explore new experiences.